Upgrading adaptation: How digital transformation promotes organizational resilience - Browder, Russell E.; Dwyer, Sean M.; Koch, Hope (Strategic Entrepreneurship Journal, 2024)
Abstract Research Summary This study explores how digital transformation can promote organizational resilience when incumbent firms face crises. We examine the intersection of digital transformation and resilience‐seeking processes through two longitudinal case studies of incumbent firms designated as “essential businesses” during the COVID‐19 pandemic. We analyze 72 crisis adaptations the firms implemented during the crisis to understand how previously underutilized digital capabilities upgraded each firm's ability to adapt to mitigate stakeholder risks and engage in resilience‐seeking rather than advantage‐ or opportunity‐seeking. We identify five digital capabilities—virtual access, virtual collaboration, data‐driven decision‐making, algorithmic reprogrammability, and assisted decision‐making—that arose from technologies acquired to enable digital transformation before the crisis. We discuss the concept of resilience opportunities and contribute to the literatures on digital transformation and organizational resilience. Managerial Summary While studying the digital transformation of incumbent firms, we found that digital capabilities helped firms adapt during the COVID‐19 pandemic in ways that crisis management plans did not anticipate. As a result, these adaptations accelerated digital transformation initiatives that years of strategic planning had failed to achieve. We explain why the quantum leap in digital transformation helped these firms not only adapt during crisis, but digital adaptation also enabled them to bounce back more resilient and competitive than before the crisis. We show how the pursuit of organizational resilience can be a vital justification for investments in digital transformation. Strategic leaders play a critical role in not only adopting new technologies, but also in helping firms become more adaptive by combining new and legacy technologies.